Values of Local Wisdom in the Traditional Tingkeban Ceremony Among the Jawa-Pangandaran Ethnic Group - Nuraini, Nia; Brata, Yat Rospia; Budiman, Agus (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2025)
The Tingkeban is a tradition handed down from the Javanese tribe which is still preserved among the Javanese people in Pangandaran. This research is to determine the implementation and express the values of local wisdom in the Tingkeban Tradition among the Javanese-Pangandaran ethnic group. The method used in this research is a qualitative method with a type of historical study (history research). The steps in historical study are Heuristics, Criticism, Interpretation, and Historiography. Apart from that, it uses the Anthropological method, namely the Socio-Cultural research method (culture domain) using triangulation in analyzing data. Data collection techniques in this research are observation, interviews and documentation. Meanwhile, the data collection used in this research is literature study and field study. The results of the research show that the traditional procession of the tingkeban ceremony is making rujak, splashing the mother-to-be, putting village eggs into the mother-to-be's cloth, changing nyamping seven times, splitting the ivory coconut, Selamatetan and serving. And the local wisdom values contained in the tingkeban traditional ceremony are increasing togetherness between generations, respect for traditions and cultural heritage, preparation for the role of parents, formation of identity and a sense of belonging, learning social values, and strengthening solidarity and cooperation.